Canadian Red [large type] - Stone, R. W. (Circle V western., 2018)
"Mountie Lucas Donovan chases a ruthless serial killer whose victims include Lucas' twin brother. Taking an administrative leave and accompanied by his malamute sled dog, Lucas crosses the border into the U.S. and faces a struggle for survival in the unfamiliar, unfriendly country. But a greater struggle is between his code of honor and his desire for revenge"--